2016
DOI: 10.1038/srep28386
|View full text |Cite
|
Sign up to set email alerts
|

Differential conformational modulations of MreB folding upon interactions with GroEL/ES and TRiC chaperonin components

Abstract: Here, we study and compare the mechanisms of action of the GroEL/GroES and the TRiC chaperonin systems on MreB client protein variants extracted from E. coli. MreB is a homologue to actin in prokaryotes. Single-molecule fluorescence correlation spectroscopy (FCS) and time-resolved fluorescence polarization anisotropy report the binding interaction of folding MreB with GroEL, GroES and TRiC. Fluorescence resonance energy transfer (FRET) measurements on MreB variants quantified molecular distance changes occurri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 46 publications
1
3
0
Order By: Relevance
“…Our results indicate that HSP10 has a chaperone function on its own, not merely functioning as a co-chaperone for HSP60. This hypothesis is supported by previous studies of folding and unfolding activity on five different substrate proteins by GroES (carbonic anhydrase, lysozyme, serum albumin, and the bacterial actin homolog MreB) ( Moparthi et al, 2014 ; Moparthi et al, 2016 ). Furthermore, the mere abundance of HSP10 in relation to HSP60 in tissue throughout the human body ( Figure 2 ) is highly suggestive of HSP10 with separate functions.…”
Section: Discussionsupporting
confidence: 74%
See 2 more Smart Citations
“…Our results indicate that HSP10 has a chaperone function on its own, not merely functioning as a co-chaperone for HSP60. This hypothesis is supported by previous studies of folding and unfolding activity on five different substrate proteins by GroES (carbonic anhydrase, lysozyme, serum albumin, and the bacterial actin homolog MreB) ( Moparthi et al, 2014 ; Moparthi et al, 2016 ). Furthermore, the mere abundance of HSP10 in relation to HSP60 in tissue throughout the human body ( Figure 2 ) is highly suggestive of HSP10 with separate functions.…”
Section: Discussionsupporting
confidence: 74%
“…This ATP-driven process utilizes the hydrophobicity of the inner part of HSP60 that attracts unfolded or misfolded proteins. Earlier studies have however suggested that HSP10 participates in initial unfolding of client proteins and deliver these to HSP60 ( Moparthi et al, 2014 ; Moparthi et al, 2016 ). HSP10 in humans is normally a mitochondrial protein but has also been found circulating in the blood stream.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fibril-forming actin homologs exist in bacteria (MreB) and archaea (crenactin) ( Figure S7) but do not strictly require their cognate chaperonin to fold (Kerner et al, 2005;Moparthi et al, 2016). The relationship of actin with TRiC is unique, and we propose that coevolution of substrate and chaperone has allowed the primary sequence of actin to diverge to the point where it can no longer fold on its own.…”
Section: Evolution Of Chaperonin Dependence Of Actinmentioning
confidence: 96%